Correlation of HbA1c with Lipid Profile in Type 2 Diabetes - Febryanto, Muhammad Desto Habibi; Pertiwi, Dian; Permana, Hendra; Kurniawan, Eka; Husni; Afriani, Nita (Rumah Sakit Umum Pusat (RSUP) Dr. M. Djamil, 2026)
Background: Type 2 diabetes mellitus (T2DM) is typically in line with dyslipidaemia, which substantially increases cardiovascular risk. Glycated haemoglobin (HbA1c) reflects long-term glycaemic control and has been proposed as a potential surrogate marker for lipid abnormalities. However, evidence regarding the correlation between HbA1c and lipid profile components remains inconsistent, particularly in Southeast Asian populations. This study aimed to evaluate the correlation between HbA1c levels and lipid profile parameters among patients with T2Dm treated at a tertiary referral hospital in Indonesia. Methods: A cross-sectional analytic study was conducted using medical record data from 68 patients with T2DM. HbA1c levels and lipid profile parameters–including total cholesterol, high-density lipoprotein (HDL) cholesterol, low-density lipoprotein (LDL) cholesterol, and triglycerides–were analysed. Data normality was assessed using the Kolmogorov–Smirnov test. Spearman’s rank correlation test was applied to determine the correlation between HbA1c and lipid profile components. Results: The median HbA1c level was 8.70% (range: 4.90–14.70%), indicating suboptimal glycaemic control. Median lipid profile values were 203.50 mg/dL for total cholesterol, 55.50 mg/dL for HDL cholesterol, 115.00 mg/dL for LDL cholesterol, and 138.50 mg/dL for triglycerides. Correlation analysis revealed no statistically significant association between HbA1c levels and any lipid profile component. Conclusion: HbA1c levels were not significantly correlated with lipid profile parameters in patients with T2DM. These findings suggest that glycaemic control alone may not adequately reflect lipid-related cardiovascular risk, underscoring the need for comprehensive cardiometabolic assessment in patients with T2DM.